Thickness measurement of nm HfO2 films - Kim, K J; Kim, A; Kim, C S; Song, S W; Ruh, H; Unger, W E S; Radnik, J; Mata-Salazar, J; Juarez-Garcia, J M; Cortazar-Martinez, O; Herrera-Gomez, A; Hansen, P E; et al. (Metrologia, 2021)
A pilot study for the thickness measurement of HfO2 films was performed by the Surface Analysis Working Group (SAWG) of the Consultative Committee for Amount of Substance (CCQM). The aim of this pilot study was to ensure the equivalency in the measurement capability of national metrology institutes for the thickness measurement of HfO2 films. In this pilot study, the thicknesses of six HfO2 films with nominal thickness from 1 nm to 4 nm were measured by X-ray Photoelectron Spectroscopy (XPS), X-ray Reflectometry(XRR), X-ray Fluorescence Analysis (XRF), Transmission Electron Spectroscopy (TEM), Spectroscopic Ellipsometry (SE) and Rutherford Backscattering Spectrometry (RBS). The reference thicknesses were determined by mutual calibration of a zero-offset method (Medium Energy Ion Scattering Spectroscopy (MEIS) of KRISS) and a method traceable to the length unit (the average thicknesses of three XRR data except the thinnest film). These reference thicknesses are traceable to the length unit because they are based on the traceability of XRR. For the thickness measurement by XPS, the effective attenuation length of Hf 4f electrons was determined. In the cases of XRR and TEM, the offset values were determined from a linear fitting between the reference thicknesses and the individual data by XRR and TEM. The amount of substance of HfO2, expressed as thickness of HfO2 films (in both linear and areal density units), was found to be a good subject for a CCQM key comparison.To reach the main text of this paper, click on Final Report. The final report has been peer-reviewed and approved for publication by the CCQM.